An Outbreak of Human Coronavirus OC43 Infection and Serological Cross-Reactivity with SARS Coronavirus. Issue 6 (1st December 2006) - Patrick, David M; Petric, Martin; Skowronski, Danuta M; Guasparini, Roland; Booth, Timothy F; Krajden, Mel; McGeer, Patrick; Bastien, Nathalie; Gustafson, Larry; Dubord, Janet; MacDonald, Diane; David, Samara T; et al.
Abstract : BACKGROUND: In summer 2003, a respiratory outbreak was investigated in British Columbia, during which nucleic acid tests and serology unexpectedly indicated reactivity for severe acute respiratory syndrome coronavirus (SARS-CoV). METHODS: Cases at a care facility were epidemiologically characterized and sequentially investigated for conventional agents of respiratory infection, SARS-CoV and other human CoVs. Serological cross-reactivity between SARS-CoV and human CoV-OC43 (HCoV-OC43) was investigated by peptide spot assay. RESULTS: Ninety-five of 142 residents (67%) and 53 of 160 staff members (33%) experienced symptoms of respiratory infection. Symptomatic residents experienced cough (66%), fever (21%) and pneumonia (12%). Eight residents died, six with pneumonia. No staff members developed pneumonia. Findings on reverse transcriptase-polymerase chain reaction assays for SARS-CoV at a national reference laboratory were suspected to represent false positives, but this was confounded by concurrent identification of antibody to N protein on serology. Subsequent testing by reverse transcriptase-polymerase chain reaction confirmed HCoV-OC43 infection. Convalescent serology ruled out SARS. Notably, sera demonstrated cross-reactivity against nucleocapsid peptide sequences common to HCoV-OC43 and SARS-CoV. CONCLUSIONS: These findings underscore the virulence of human CoV-OC43 in elderly populations and confirm that cross-reactivity to antibody against nucleocapsid proteins from these viruses must be considered when interpreting serological tests for SARS-CoV.